Kerendahhatian dan Pemaafan pada Mahasiswa - Yogi Kusprayogi; Fuad Nashori (Psikohumaniora: Jurnal Penelitian Psikologi, 2016)
Abstract: This study aims to determine the correlation between humility and forgiveness in students. Respondents in this research are 252 students majoring in Psychology, Faculty of Psychology and Social and Cultural Sciences, Islamic University of Indonesia, with ages range from 17 to 24 years old. The hypothesis put forward by researchers is that there is positive correlation between the variables of humility and forgiveness in students. The research data in this study were analyzed using analytical techniques and product moment correlation from Karl Pearson; that is used to examine the relation between variables. The results showed that there is a positive correlation between humility and forgiveness (r = 0. 508 and p 0. 05) with the contribution of humility on the forgiveness of 25. 8%. Other results showed that there are different aspects of humility that contribute to forgiveness, in terms of demographic variables of age and gender.Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan kerendahhatian dan pemaafan pada mahasiswa. Responden dalam penelitian ini adalah 252 mahasiswa jurusan psikologi, Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia, dengan rentang usia 17-24 tahun. Hipotesis yang diajukan peneliti adalah adanya hubungan positif antara variabel kerendahhatian dan pemaafan pada mahasiswa. Data yang diperoleh dalam penelitian dianalisis dengan menggunakan teknik analisis dan korelasi product moment dari Karl Pearson yang digunakan untuk melihat hubungan antar variabel. Hasil penelitian menunjukkan bahwa ada korelasi positif antara kerendahhatian dan pemaafan(r= 0, 508 dan p0, 05) dengan kontribusi variabel kerendahhatian pada pemaafan sebesar 25, 8%. Hasil lainnya menunjukkan ada perbedaan aspek kerendahhatian yang berkontribusi pada pemaafan ditinjau dari variabel demografi usia dan jenis kelamin.